Right mini‐thoracotomy approach for grown‐up congenital heart disease. Issue 6 (26th February 2021) - Barbero, Cristina; Marchetto, Giovanni; Pace Napoleone, Carlo; Calia, Claudia; Cura Stura, Erik; Pocar, Marco; Rinaldi, Mauro; Boffini, Massimo
Abstract: Background: Right mini‐thoracotomy cardiac surgery has been recognized as a safe and effective procedure, with remarkable early and long‐terms outcomes. However, most of the literature is focused on mitral valve surgery and few studies report on the minimally invasive approach applied to congenital disease. Aim of this study was to review our experience on patients with grown‐up congenital heart (GUCH) undergoing right mini‐thoracotomy cardiac surgery. Methods: Data of patients with GUCH undergoing right mini‐thoracotomy cardiac surgery from 2006 to 2019 were retrospectively analyzed. Inclusion criteria were atrial septal defect, partial anomalous pulmonary venous return, partial atrioventricular septal defect, and mitral or tricuspid valve dysfunction in congenital heart diseases. Results: During the study period 127 patients with GUCH underwent right mini‐thoracotomy cardiac surgery. Mean age was 43.6 years and more than 60% were females; diagnosis was atrial septal defect in 57 cases (44.9%); 24 patients were redo (18.9%). No cases of stroke and major vascular complications were reported. Conversion to sternotomy was required in one case (0.8%). No residual shunts or valves dysfunction were recorded at the postoperative echocardiographic evaluation. Perioperative mortality was 1.6%. Conclusions: Right mini‐thoracotomy cardiac surgery in selected patients with GUCH allows to avoid the big scar of the sternotomy approach and to accelerate the recovery in a young population. Moreover, in redo cases, it allows the surgeon to reach the heart and the aorta avoiding the well‐known risks of a re‐sternotomy procedure.